2016
DOI: 10.1007/s00380-016-0919-6
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of brachial-ankle pulse wave velocity in predicting long-term cardiovascular events in younger patients

Abstract: Brachial-ankle pulse wave velocity (baPWV) is known as a significant predictor of cardiovascular events. However, the previous studies have not considered age, which can affect the baPWV value. We evaluated the predictive value of baPWV for cardiovascular events in various age groups. From January 2005 to December 2012, all patients admitted to our department with any cardiovascular disease and underwent ankle-brachial index (ABI) measurement were enrolled in the IMPACT-ABI registry. The primary endpoints incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…With respect to different age groups, a significant association between high baPWV and CV events was noted in younger patients (30-59 years); on the contrary, such relations were not observed in older age groups, suggesting a potential predictive significance of baPWV in younger patients. 10 Similar associations have been found in studies of patients with overt CV disease. In patients with non-ST-elevation myocardial infarction, major CV events and CV mortality were higher in patients with high baPWV (17 m/s) compared with patients with lower values.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…With respect to different age groups, a significant association between high baPWV and CV events was noted in younger patients (30-59 years); on the contrary, such relations were not observed in older age groups, suggesting a potential predictive significance of baPWV in younger patients. 10 Similar associations have been found in studies of patients with overt CV disease. In patients with non-ST-elevation myocardial infarction, major CV events and CV mortality were higher in patients with high baPWV (17 m/s) compared with patients with lower values.…”
supporting
confidence: 75%
“…Among all participants, the risk for major CV events was significantly increased in the high, compared with the low, baPWV group. With respect to different age groups, a significant association between high baPWV and CV events was noted in younger patients (30‐59 years); on the contrary, such relations were not observed in older age groups, suggesting a potential predictive significance of baPWV in younger patients …”
mentioning
confidence: 91%
“…Details of the IMPACT-ABI study have been published. [14][15][16][17] In summary, we retrospectively identified 4,619 consecutive patients who were admitted to the Department of Cardiology at Shinshu University Hospital for any CV disease between January 2005 and December 2012. Of these, 1,488 patients were excluded because of missing ABI data, and the remaining 3,131 patients were enrolled in the IMPACT-ABI study.…”
Section: Study Populationmentioning
confidence: 99%
“…In fact, previous studies have shown that central arterial stiffness is a strong predictor of cardiovascular mortality in patients with ESRD 17,19 . Of note, there is also enough literature evidence demonstrating that the baPWV is an independent predictor of cardiovascular events and mortality [20][21][22][23][24][25] . However, theoretically, the baPWV, which reflects peripheral arterial stiffness, is limited in predicting cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%